Handgrip Strength in Fibromyalgia - Kurtuluş KÖKLÜ; Merve SARIGÜL; Zuhal ÖZİŞLER and Hülya ŞİRZAİ and Sumru ÖZEL (Archives of Rheumatology, 2016)
Objectives: This study aims to compare the handgrip strength values of fibromyalgia (FM) patients and healthy individuals and to demonstrate the relationship between clinical factors and FM disease severity. Patients and methods: Twenty-five female patients (mean age 34±9.2 years; range 20 to 50 years) with FM and 23 age- and body mass index-similar healthy females (mean age 35.3±9.2 years; range 26 to 46) were included. Demographic characteristics of the subjects were recorded. Tender point count was noted in the patient group. Also; total myalgia score and fibromyalgia impact questionnaire scores were calculated. Handgrip strength was measured with Jamar® dynamometer. Patients who had fibromyalgia impact questionnaire scores ≥70 out of 100 were considered to have severe FM, while those who had scores <70 were considered to have moderate FM. Results: There were no significant differences between the patient and control groups in terms of age, height, weight, and body mass index. However, patients’ handgrip strength values were lower than those of the control group (p=0.011). In the patient group, positive correlation was only present between handgrip strength and body mass index values (r= -0.510, p=0.037). There was no significant difference between moderate and severe FM patients in terms of handgrip strength values. Conclusion: Fibromyalgia patients had decreased handgrip strength when compared to healthy subjects. Handgrip strength values of moderate and severe FM patients were similar. FM severity was correlated with body mass index and severity of myalgia.